In Praise of Descriptive Science: A Breath of Fresh AIRE - Davis, Mark M. (Cell, 2016)
Meyer et al. find that subjects lacking the AIRE gene, critical for self-tolerance in T lymphocytes, show a broad range of autoantibody specificities, which can have extremely high affinities. The data also suggest that some of these autoantibodies can, surprisingly, prevent some types of autoimmunity, particularly type I diabetes. Subjects lacking the AIRE gene, critical for self-tolerance in T lymphocytes, show a remarkably broad range of autoantibody specificities, some of which have much higher affinities than what is typical. The data also suggest that some of these autoantibodies can, surprisingly, prevent some types of autoimmunity, particularly type I diabetes.